2007
DOI: 10.1007/s00420-007-0228-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioaerosol exposure on work-related symptoms among Swiss sawmill workers

Abstract: Objective Exposure to bioaerosols in the occupational environment of sawmills could be associated with a wide range of health eVects, in particular respiratory impairment, allergy and organic dust toxic syndrome. The objective of the study was to assess the frequency of medical respiratory and general symptoms and their relation to bioaerosol exposure. Method Twelve sawmills in the French part of Switzerland were investigated and the relationship between levels of bioaerosols (wood dust, airborne bacteria, air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…In order to gain an understanding of the magnitude of these problems, research has been done measuring the levels of fungi as well as other microorganisms and -particles in workplaces such as farms (Radon et al 2002) and sawmills (Rusca et al 2008). Most occupational environment research, however, has focused on sampling indoor workplaces with a few outdoor samples for reference.…”
Section: Introductionmentioning
confidence: 99%
“…In order to gain an understanding of the magnitude of these problems, research has been done measuring the levels of fungi as well as other microorganisms and -particles in workplaces such as farms (Radon et al 2002) and sawmills (Rusca et al 2008). Most occupational environment research, however, has focused on sampling indoor workplaces with a few outdoor samples for reference.…”
Section: Introductionmentioning
confidence: 99%
“…Most species of the fungi spores found in the coal mine air samples and on organic material, such as timber safety structures built in the galleries, can produce mycotoxins that can cause different diseases when introduced into the human body (Rusca et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although bacterial communities and endotoxin concentrations have been reported in several studies (Gorny and Dutkiewicz 2002;Park et al, 2002;Herr et al, 2003;Oppliger et al, 2005;Rusca et al, 2008;Tendal and Madsen, 2011), only a few studies have evaluated their relationships with the types of land use (Mueller-Anneling et al, 2004;Madsen, 2006;Bowers et al, 2010;Tager et al, 2010;Woo et al, 2013). In a study designed to investigate the risk factors of childhood asthma, air samples were collected from several locations throughout Fresno, a city in central California, USA; the study revealed that the endotoxin concentrations varied among various geographical regions.…”
Section: Introductionmentioning
confidence: 99%